Fully jointed rack without the use of fasteners / Muhammad Faizal Musa - Musa, Muhammad Faizal (2013)
In this study, Blockboard has been used to produce the fully jointed rack without using any fasteners. The production of this product has been used cross lap joint that required good machining properties in order to get perfect surfaces. The jointing system is quiet difficult due to the angle that needs to be made and the product must be in triangle form. Blockboard has been used as a raw material to produce the product because it is light weight, cheap and has good machining properties. The product was determined as Do It Yourself (DIY) product because it is easy to assemble and easy to carry out. The results of the product that get it from correspondents shows that this product easy to assembled without using any fastener such as nail and screw and low in cost with high quality. Most of the peoples choose this product as a place to load books.